Changes in Seed Quality during Seed Development and Maturation of Bambara Nut (Vigna subterranea (L.) Verdc.) Landraces - Gerard Oballim; Morish Obura; Wilson Reuben Opile; Julius Onyango Ochuodho (International Journal of Agronomy)
This study aimed at determining changes in the seed quality of bambara nut (BN) landraces during seed development and maturation so as to more precisely time seed harvest for better seed quality. Three bambara nut landraces, AbiBam001, LocalBam, and TVSU544, were sown in two field experimental sites in northern Uganda in October 2020 and 2021. Seeds were harvested at 83, 93, 103, 113, and 123 days after sowing (DAS) in the first experiment and at 123, 130, and 138 DAS in the second. Seeds were subjected to quality tests of seed dry weight, final germination percentage (FGP), germination velocity index (GVI), and seedling dry weight (SDW). All landraces showed significant differences P < 0.05 in seed weight and seedling dry weight at progressive developmental stages in the first experiment. All parameters showed no differences P > 0.05 in the second experiment except for the seed weight of AbiBam001 and the FGP of TVSU544. Both TVSU544 and LocalBam attained mass maturity (highest seed weight) at approximately 113 DAS, while AbiBam001 reached mass maturity at about 130 DAS. Seeds of the highest quality were obtained at 103 DAS for TVSU544 and at 113 DAS for both LocalBam and AbiBam001. For both AbiBam001 and TVSU544, the highest quality seeds occur before mass maturity, while for LocalBam, at about mass maturity. Seed harvest should be timed at 103−113, 113−123, and 120−130 DAS for TVSU544, LocalBam, and AbiBam001, respectively. The assessment of seed development before 83 DAS and maturation after 138 DAS in the main growing season will synchronize growing conditions with farmers’ practices and crucially provide a complete picture of the developmental patterns of the landraces.